2021
DOI: 10.1016/j.anr.2021.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Behaviors Toward End-of-life Care Among Chinese Oncology Nurses: A Cross-Sectional Study

Abstract: The goal of this study was to describe the current status of oncology nurses' behaviors toward EOL care in China and to explore the factors associated with oncology nurses' behaviors toward EOL care. Methods: A cross-sectional design was applied and a convenience sample of 1038 oncology nurses from 22 grade A hospitals were recruited into this study. A general social demographic data questionnaire was administered, and the Chinese version of Nurses' Behaviors of Caring for Dying Patients Scale was used to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…First, perceived susceptibility had the most dramatic effect among three dimensions, indicating that nurses always felt upset, anxious, weak, hopeless, guilty, suffocated, and grieved and were unable to easily face the dying process of coping with patient death, which was unanimous with another study ( 28 ). Second, perceived barriers had indirect effects on practices, showing that nurses who had more perceived difficulties concerning palliative care had lower behavior, which was consistent with a previous study ( 29 ). Finally, perceived benefits had an indirect effect on practices.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…First, perceived susceptibility had the most dramatic effect among three dimensions, indicating that nurses always felt upset, anxious, weak, hopeless, guilty, suffocated, and grieved and were unable to easily face the dying process of coping with patient death, which was unanimous with another study ( 28 ). Second, perceived barriers had indirect effects on practices, showing that nurses who had more perceived difficulties concerning palliative care had lower behavior, which was consistent with a previous study ( 29 ). Finally, perceived benefits had an indirect effect on practices.…”
Section: Discussionsupporting
confidence: 90%
“…Despite the frequent phenomenon of knowing without doing, the great majority of researchers hold the view that the effect of knowledge on practices is worth affirming fully and permanently among other factors (26). Previous study showed that the lack of adequate end-of-life and legal literacy training for nurses was a key reason why the overall knowledge of health service providers in Shanghai was generally moderate (21) and a lack of adequate training on end-of-life will and legal knowledge for nurses is a key reason (27). Consequently, it is highly necessary for nurses, the major primary health service providers in diversified nursing, to systematically learn theoretical knowledge in palliative care, strengthen education on life and death, and improve the understanding of the concept and significance of palliative care services.…”
Section: Discussionmentioning
confidence: 99%
“…Commensurate oncology nursing must match this rapid increase in cancer incidence and mortality in palliative care, end-of-life care, and pain management. However, even though cancer is the leading cause of death in China, little was known about cancer-related end-of-life care until recently, when it began receiving increasing attention ( 60 , 61 ).…”
Section: The Development and Practice Of Oncology Nursing In Chinamentioning
confidence: 99%
“…Given the unique cultural context in China, comprehending the experiences of multidisciplinary teamwork in implementing humanistic care for patients with cancer may have varied implications for healthcare professionals. While various studies have delved into nurses’ attitudes and behaviours in caring for oncology patients,23 24 few qualitative enquiries have explored the experiences of multidisciplinary teams collaborating to provide care for such patients and implement humanistic care 25. Therefore, this qualitative study aimed at gaining a deeper understanding of the humanistic experiences of palliative care provision among medical staff in oncology wards.…”
Section: Introductionmentioning
confidence: 99%